Characterization of ancient ceramic shreds: Insights into firing conditions and manufacturing technology - Mammadov, S.; Gurbanov, M.; Ahadova, A.; Abishov, A. (Recent Research in Science and Technology, 2023)
Four ancient ceramic shreds from the archaeological site Leletepe in the Fizuli region of the Republic of Azerbaijan and two local raw ceramic pastes were characterized by powder X-ray diffraction (PXRD) and thermal analysis (TG-DTG) techniques. XRD analysis of ceramic sherds reveals that all investigated samples contain similar minerals: quartz, feldspar, and clay. Three samples out of four contain calcite. Based on the traditional approach, it has been assumed that the firing process in these samples stopped before 700 °C. The mass loss ratios of samples of ancient ceramics also indicate that reversible dehydroxylation took place in all four samples, thus indicating the initial mild firing conditions. The summary of all the applied methods indicates that the ceramic samples were made using a similar manufacturing technology. According to XRD analysis, samples N1 and N4 contain diopside, and samples N2 and N3 contain maghemite, indicating the different origins of the ceramic shreds. Analysis of the raw ceramic mass also did not reveal the presence of these minerals, which may indicate a discrepancy between the origin of ancient ceramic sherds and modern ones.